Calcitriol Inhibits Viability and Proliferation in Human Malignant Pleural Mesothelioma Cells - Gesmundo, Iacopo; Silvagno, Francesca; Banfi, Dana; Monica, Valentina; Fanciulli, Alessandro; Gamba, Giacomo; Congiusta, Noemi; Libener, Roberta; Riganti, Chiara; Ghigo, Ezio; Granata, Riccarda (Frontiers in Endocrinology, 2020)
Malignant pleural mesothelioma (MPM) is a rare and aggressive tumor, often associated with exposure to asbestos and characterized by poor prognosis and limited treatment options. The biologically active form of vitamin D, calcitriol, exerts anticancer effects in many cell types, both alone and in combination with chemotherapy drugs, through binding to vitamin D receptor (VDR); however, the role of calcitriol in MPM is still unknown. This study aimed to determine the potential antitumor role of calcitriol in MPM. The results showed that calcitriol reduces cell viability and proliferation in human MPM cells lines, which express both cytoplasmic and nuclear VDR; furthermore, calcitriol potentiated the inhibitory activity of the chemotherapy drug PEM. These effects were paralleled by cell cycle arrest and inhibition in expression of c-Myc and cyclins involved in cell cycle progression. Exposure of MPM cells to calcitriol also produced an alteration in mitochondrial function and inhibition in the expression of respiratory chain complex subunits. Finally, the inhibitory effects of calcitriol were also observed on viability of human primary MPM cells. Collectively, these results indicate a novel anticancer role for calcitriol in MPM, suggesting potential for vitamin D derivatives, alone or in combination with chemotherapy, in the treatment of this malignancy.